Syntheses, single crystal structures, DFT and antioxidant superoxide dismutase studies of some new mono-/binuclear copper(II) complexes. (17th June 2017) - Patel, R.N.; Singh, Yogendra Pratap; Singh, Yogendra; Butcher, Ray J.; Jasinski, Jerry P.
Graphical abstract: Mono- and binuclear copper(II) complexes have been synthesized using HL 1 and other mono and bidentate ligands (L 2 ). Interest in exploring metal complexes with ligands has continually increased, since the recognition that many of these materials may serve as models which mimic both the structure and reactivity of metal ion sites in complex biological systems and possess a broad spectrum of biological activity. Abstract: A series of mono- and binuclear copper(II) complexes have been synthesized using HL 1 and other mono- and bidentate ligands (L 2 ) [HL 1 = N ′-[( E )-phenyl(pyridin-2-yl)methylidene]thiophene-2-carbohydrazide, L 2 = 2-benzoyl pyridine (BP), neocuprin, imidazole (ImH) and pyrazine] by a one pot synthesis. These complexes were characterized by routine physico-chemical techniques. The single crystal X-ray structures of1, 2, 3 and5 were determined. X-ray single crystal analyses reveal that complex1 is six coordinated while complex2 is a penta coordinated complex. Complex3 is pseudo binuclear while4 and5 are binuclear complexes. Intermolecular π…π stacking interactions could be detected in the solid medium and classical H-bonding interactions lead to infinite 1D chains and to an infinite 2D network in2 . Variable temperature magnetic susceptibility data display antiferromagnetic couplings in3 –5 . The X-band epr spectra for polycrystalline samples of3 –5 exhibit copper(II) hyperfine structure as well as zero-field splitting which are appropriate for the triplet state of such a dimer. Epr data also indicate antiferromagnetic behavior for binuclear complexes3 –5 . Binuclear complexes were also studied using cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The conproportion constant ( K con ) of complexes3 –5 have been evaluated and discussed. Modeling by DFT and TD-DFT is done to elucidate the nature and location of the excited state in superoxide dismutase (SOD) mimics. In addition, antioxidant SOD activity showed that HL 1 and its copper(II) complexes possess significant scavenging effect against O2 − free radicals.